Konsep Pengajaran Islam Menurut K.H. Hasyim Asy’ari - Alwi, Wildan; Alwizar; Kadar; Mubarok, M. Naelul (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2022)
This research aims to determine the concept of Islamic education, and the contribution of KH. Hasyim Asy'ari, so the author finds the shortcomings and strengths in Educational thinking according to KH. Hasyim Asy'ari. The research method used in this study is the Library Research method, which is a series of activities related to the method of collecting library information, reading and writing and processing research material. The data analysis technique that the author uses in this research is content analysis or what is often referred to as content analysis. This content analysis is used to compare one research with other research according to this article. It is a research that uses library sources from articles and journals to obtain research information. This research has a problem formulation including, How is the concept of Islamic education according to KH. Hasyim Asy'ari? and How the contribution of KH. Hasyim Asy'ari in the development of education today. The results of this study define the thinking of KH. Hasyim Asy'ari so that it produces a concept of Islamic education and the contribution of KH. Hasyim Asy'ari